1998
DOI: 10.1007/s007020050108
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of advanced glycation endproducts is mediated by oxidative stress

Abstract: Non-enzymatic glycation of proteins with reducing sugars and subsequent transition metal catalysed oxidations leads to the formation of protein bound "advanced glycation endproducts" (AGEs). They accumulate on long-lived proteins and are for example structural components of the beta-amyloid plaques in Alzheimer's disease. Since the oxidation of glycated proteins as well as the interaction of AGEs with cell surface receptors produces superoxide radicals, it was tested in BHK 21 hamster fibroblast cells and SH-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 22 publications
3
83
0
1
Order By: Relevance
“…The AGE have been implicated in nerve damage with much work done on the aetiology of Alzheimer's disease and the glycation of amyloid-b protein, which is a precursor of the senile plaque seen in this condition [116]. As with diabetic retinopathy there is evi-dence of vascular dysfunction and that includes accumulation of AGE in the vasa nervorum leading to wall thickening, ischaemia, occlusion [117] and myelin damage with segmental demyelination [35].…”
Section: Thrombosis and Fibrinolysis Tissue Factor Thrombomodulinmentioning
confidence: 99%
“…The AGE have been implicated in nerve damage with much work done on the aetiology of Alzheimer's disease and the glycation of amyloid-b protein, which is a precursor of the senile plaque seen in this condition [116]. As with diabetic retinopathy there is evi-dence of vascular dysfunction and that includes accumulation of AGE in the vasa nervorum leading to wall thickening, ischaemia, occlusion [117] and myelin damage with segmental demyelination [35].…”
Section: Thrombosis and Fibrinolysis Tissue Factor Thrombomodulinmentioning
confidence: 99%
“…However, it could be prevented by treatment with an antioxidant, pointing to oxidative stress as a cause of cell death. Since AGEs and oxidative stress have been linked [30] and endogenous NO is known to contribute to intracellular oxidative stress [31], we investigated oxidative stress markers in SH-SY5Y cells. Indeed we have found that the highest increase in ROS upon exposure to AGEs occurred in nNOS-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…MTT enters the cells by endocytosis and is reduced to formazan by NADH reductase and other enzymes in a reaction that can be measured spectrophotometrically. The amount of formazan reflects the reductive potential of the cytoplasm and the cell viability and generally shows good correlation with other viability tests (30,39,40). Live/dead assays were performed following the protocol provided by the kit (live/dead viability/cytotoxicity kit for mammalian cells; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%